Radiation damage studies in cardiac muscle cells and tissue using microfocused X‐ray beams: experiment and simulation. (17th June 2019) - Nicolas, Jan-David; Aeffner, Sebastian; Salditt, Tim
Abstract : Highly dose‐demanding experiments on soft tissue using microfocused or nanofocused X‐ray beams require a careful assessment of the tolerable dose. Experimental evidence for detrimental dose effects can be supplemented by Monte Carlo simulations that can give additional guidance to the experimenter for a maximally dose‐efficient planning of future experiments. Abstract : Soft materials are easily affected by radiation damage from intense, focused synchrotron beams, often limiting the use of scanning diffraction experiments to radiation‐resistant samples. To minimize radiation damage in experiments on soft tissue and thus to improve data quality, radiation damage needs to be studied as a function of the experimental parameters. Here, the impact of radiation damage in scanning X‐ray diffraction experiments on hydrated cardiac muscle cells and tissue is investigated. It is shown how the small‐angle diffraction signal is affected by radiation damage upon variation of scan parameters and dose. The experimental study was complemented by simulations of dose distributions for microfocused X‐ray beams in soft muscle tissue. As a simulation tool, the Monte Carlo software package EGSnrc was used that is widely used in radiation dosimetry research. Simulations also give additional guidance for a more careful planning of dose distribution in tissue.